A model for managing logistics costs throughout a product’s life cycle: a case study of a multinational manufacturing company - Škerlič, Sebastjan; Sokolovskij, Edgar (Transport, 2019)
The goal of the study is to develop a model that focuses on managing logistics costs at all stages of a product’s life cycle. The model includes several different cost components and provides a wider coverage of individual processes, as logistics costs are present in different areas of a company’s operations. The applicability of the proposed method was tested in a multinational company that manufactures furniture fittings on a randomly selected product. The test results provide a theoretical and practical confirmation of the necessity to manage the logistics costs for an individual product, since other models are focused exclusively on the cost optimisation of individual logistics processes. The model therefore complements the existing knowledge and represents a practical tool for logistics professionals that enables more efficient logistics costs planning at an early stage in the development of a product, which can result in the long-term reduction in the total costs of logistics and improve the quality of business processes.First published online 28 August 2019